Content Validity of Assessment Instrument and Storyboard Two-Tier Virtual Reality (TTVR) in Acid Base Material - Astuti, Yuli; Yamtinah, Sri; Saputro, Sulistyo; Shidiq, Ari Syahidul; Sudarmin, Sudarmin; Rahayu, Sri (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2025)
The aim of this research is to analyze the content validity of the TTVR assessment instrument for acid‒base materials based on the Aiken validity index. This ensures that the instrument can effectively measure what it intends to assess. Content validity data were obtained from seven experts, including two chemistry education lecturers from UNS and five high school teachers in Surakarta. The content validity test used a 1‒4 rating scale, with categories defined as follows: relevant with a score of 4; less relevant with a score of 3; irrelevant with a score of 2; and quite relevant with a score of 1. This scale was applied to 15 instrument questions and 16 storyboard indicators related to media and material aspects. The development results of the TTVR assessment instrument for acid‒base content achieved an Aiken index of over 0.76, indicating that the instrument is valid. This suggests that the TTVR assessment instrument and storyboard are suitable, with improvements made based on suggestions and feedback from experts.